Impact of cardiovascular risk factors on severity of peripheral artery disease. Issue 1 (September 2015) - Wyss, Thomas R.; Adam, Luise; Haynes, Alan G.; Kucher, Nils; Silbernagel, Guenther; Do, Dai-Do; Schmidli, Juerg; Baumgartner, Iris
Abstract: Objective: The development of peripheral artery disease is affected by the presence of cardiovascular risk factors. It is unclear, whether particular risk factors are leading to different clinical stages of peripheral artery disease. The aim of this retrospective cross-sectional study was to assess the association of cardiovascular risk factors with the presence of critical limb ischaemia. Methods: The study cohort was derived from a consecutive registry of patients undergoing endovascular therapy in a tertiary referral centre between January 2000 and April 2014. Patients undergoing first-time endovascular intervention for chronic peripheral artery disease of the lower extremities were included. Univariate and multivariate logistic regression models were used to assess the association of age, sex, diabetes mellitus, hypertension, dyslipidaemia, smoking, and renal insufficiency with critical limb ischaemia vs. intermittent claudication. Results: A total of 3406 patients were included in the study (mean age 71.7 ± 11.8 years, 2075 [61%] male). There was a significant association of age (OR 1.67, 95%-CI 1.53–1.82, p < 0.001), male gender (OR 1.23, 95%-CI 1.04–1.47, p = 0.016), diabetes (OR 1.99, 95%-CI 1.68–2.36, p < 0.001) and renal insufficiency (OR 1.62, 95%-CI 1.35–1.96, p < 0.001) with the likelihood of critical limb ischaemia. Smoking was associated with intermittent claudication rather than critical limb ischaemia (OR 0.78, 95%-CI 0.65–0.94, p = 0.010), while hypertension and dyslipidaemia did not show an association with critical limb ischaemia. Conclusions: In peripheral artery disease patients undergoing first-time endovascular treatment, age, male gender, diabetes, and renal insufficiency were the strongest predictors for the presence of critical limb ischaemia.